Forms of psycho-pedagogical work to overcome the negative factors in professional self-determination of teenagers with deviant behavior - Nikitskaya, E. (Psihologiâ i pravo, 2017)
The article examines the problem of professional orientation of students of adolescence with deviant behavior in secondary school. The author emphasizes the importance of understanding that without psycho-pedagogical assistance to professional orientation component development of "difficult" teenagers is very difficult and often even impossible. These difficulties caused by both objective reasons – the complexity of the process of professional selection in the current socio-economic situation and subjective age and personality characteristics of adolescents with deviant behavior. In this regard, the article describes the main factors affecting the formation of deviant adolescents the ability to professional self-determination, and proposes to the understanding and application of some form of psycho-pedagogical work on overcoming difficulties in professional self-determination of this category of students. The forms were tested in real teaching practice. В статье анализируется проблема профессионального самоопределения обучающихся подросткового возраста с девиантным поведением в условиях общеобразовательной школы. Автором подчеркивается важность понимания того, что без психолого-педагогической помощи профориентационная составляющая развития «трудных» подростков является весьма затруднительной, а зачастую и вовсе невозможной. Данные трудности обусловлены как объективными причинами – сложностью процесса профессионального выбора в современной социально-экономической ситуации, так и субъективными – возрастными и личностными особенностями подростков с девиантным поведением. В связи с этим в статье описываются основные факторы, негативно влияющие на формирование способности девиантных подростков к профессиональному самоопределению, а также предлагаются к осмыслению и применению некоторые формы психолого-педагогической работы по преодолению трудностей в профессиональном самоопределении этой категории обучающихся. Предлагаемые формы прошли апробацию в реальной педагогической практике.